(untitled) (Vietnam Journal of Community Medicine, 2025)
Background: Elderly people (NCTs) are respected by their families and society and maked active contributions to the construction and defense of the country. However, recently statistics and studies showed that, the elderly are still among the most vulnerable and poorest populations. Objective: Description of the quality of life among elderly people at Van An, Chi Linh, Hai Duong and Vinh Tien, Kim Boi, Hoa Binh, in 2020-2021. Methods: Cross-sectional study. The study collected information from 622 elderly people (NCTs) in 2 communes of Hoa Binh and Hai Duong provinces through standardized WHOQoL-100 questionnaires in Vietnam. The questionnaires included 75 questions with 6 concepts of quality of life. Data were entered by Epidata 3.1 and analyzed by SPSS 20.0. Results: The finding showed that, the mean score of QoL in elderly people was 224,6 ± 33,6 (equivalent to 6,96/10 points). 5,3% of elderly people had good QoL and 9,5% of elderly people had poor QoL. The concept that had the highest QoL was mental health, the support relationship in daily life (with 8.1/10 points) and the lowest QoL was the economic (with 5.8/10 points). The other concepts had average QoL (from 6.0/10 to 8.0/10 points).